Cytocompatibility of Caffeic Acid‐Silica Hybrid Materials on NIH‐3T3 Fibroblast Cells. Issue 1 (15th February 2021) - Catauro, Michelina; Poggetto, Giovanni Dal; Crescente, Giuseppina; Piccolella, Simona; Pacifico, Severina
Abstract: The hydroxycinnamoyl compound caffeic acid (CA), broadly occurring in plants, is receiving special attention in materials science thanks to its antioxidant, anti‐inflammatory, and antimicrobial activities that make it promising for application use in various sectors. In this context, CA–based peptide biomaterials are recently developed as eco‐friendly and multifunctional free radical scavengers useable in a wide range of consumer manufacture, ranging from cosmetics to household products, as well as clinical applications, including imaging, drug delivery, and disinfection. Furthermore, a water‐soluble chitosan‐caffeic acid conjugate, effective in delaying lipid oxidation, is also synthetized. Herein, exploiting sol‐gel route versatility, CA/silica materials are synthetized. Hybrids, chemically characterized mainly through spectroscopic techniques, varied in their relative CA content, which represented 5%, 10%, 15%, or 20% of materials' weight. The synthetized materials are able to elicit anti‐radical properties. The CA amount appeared to be determinant in anti‐radical activity, as well as in biocompatibility assessment. To this latter purpose, mouse embryonic fibroblast cell line NIH‐3T3 cells are utilized and directly exposed to hybrid materials. Redox mitochondrial activity is evaluated by means of the MTT test, whose results are in accordance with the materials' biocompatibility.